Mechanical and physical properties of acacia mangium spp forwood cement board relation to particle size and cement ratio / Mohamad Dzulhelme Hairuddin - Hairuddin, Mohamad Dzulhelme (Faculty of Applied Sciences, 2015)
ABSTRACT Mechanical and Physical properties of Acacia Mangium for wood cement board relation to particle size and cement This research was performed to determine the properties of wood cement board (WCB) made from Acacia mangium Wood.The different wood of particle size (0.5mm,1.0mm and 2.0mm) and Wood cement ratio (1:25 and 1:30) was applied.The target of board density was 1300kg m3.The physical (water absorption test and thickness swelling) and mechanical (bending test and internal bending test) properties of the WCB were evaluated.From the research, it showed that there is no significant different in physical and mechanical properties of WeB except for internal bonding in different test using the particle size.The result for modulus of rupture(MOR),water absorption and thickness swelling meet the requirement standard of MS544:2001.The application of different wood cement ratio also showed same result pattern,where there is different no significant for all testing.However wood cement ration 1:2.5 force feeds better (MOR) then compared to 1:3.0.Higher content cement causes a general decrease in MOR,WA and TS. Keyword: Acacia mangium wood